Prevalence and determinants of cigarette smoking and smoking frequency among people with tuberculosis in Lesotho: Evidence from a nationwide cross-sectional survey - Calista Ogechukwu Dozie-Nwakile; Alphonsus Ogbonna Ogbuabor; Nwanneka Chidinma Ghasi; Daniel Chukwuemeka Ogbuabor (PLoS ONE, 2026)
Background Low- and middle-income countries face a significant dual burden of tuberculosis (TB) and cigarette smoking. Nevertheless, studies examining the prevalence and determinants of smoking status and frequency among people with TB (PWTB) are scarce in sub-Saharan Africa, including Lesotho. Therefore, this study evaluated the prevalence and determinants of smoking status and frequency among people with TB in Lesotho. Methods Data on people with TB from the 2023 Lesotho Demographic and Health Survey were used in this study (n = 326). The data were adjusted for sampling weight, stratification, and cluster sampling design. The outcome variables were smoking status and smoking frequency (daily smoking and occasional smoking). The independent variables included socio-demographic factors, household characteristics, alcohol use, TB-related stigma, and mental health status. We evaluated the association between outcome and predictor variables using Pearson’s chi-squared test and complex sample logistics regression. Statistical significance was set at a p-value < 0.05. Results The prevalence of cigarette smoking among PWTB is 23.8%. The prevalence of daily and occasional smoking among PWTB is 17.3% and 6.5%, respectively. Being male (AOR = 107.48, 95%CI:22.65-510.03, p < 0.001), no media exposure (AOR = 3.65, 95%CI:1.43-9.30, p = 0.007), and alcohol use (AOR = 6.98, 95%CI:2.21-22.05, p = 0.001) increased the odds of smoking among PWTB. Being male (AOR = 211.28, 95%CI:25.86-1725.91, p < 0.001), no media exposure (AOR = 3.95, 95%CI:1.27-12.26, p = 0.018), and alcohol use (AOR = 15.10, 95%CI:3.36-67.89, p < 0.001) increased the odds of daily smoking among PWTB. Being male (AOR = 39.98, 95%CI:4.76-335.88, p = 0.001) increased the odds of occasional smoking among PWTB. Depression did not significantly influence smoking status of people with TB. Conclusion The prevalence of smoking among PWTB is high in Lesotho. Our findings underscore the importance of gender-sensitive tobacco use prevention and control interventions among PWTB, an inclusive and adequately funded long-term plan for best-practice anti-tobacco media campaign, and integrating management of substance use disorder into TB control policy and routine TB care in Lesotho.